2001
DOI: 10.1051/0004-6361:20010588
|View full text |Cite
|
Sign up to set email alerts
|

The source of the solar oscillations: Convective or magnetic?

Abstract: Abstract. The origin of solar oscillations has not yet been clearly determined. The downflows due to convective rapid cooling at the surface have been invoked as a possible source. In this paper we investigate the properties of the source as inferred from the local analysis of the intensity-velocity phase differences. The same spatial and temporal characteristics of other observed events and their correlation with the Hα bright points suggests downward plasma jets related to explosive chromospheric evaporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The explosive chromospheric evaporation model (Fisher et al 1985) explains the main observed characteristics of those events whose spatial scales are of the order of a few arcsec and last for a few minutes . The same scales are those obtained by the analysis of the background locations maintaining spatial resolution (Moretti et al 2001a). Recently, observations in Hα and NaI D lines have shown a simultaneous occurrence of the impulsive brightenings (Warmuth et al 2000;Moretti et al 2001b).…”
Section: The Observationssupporting
confidence: 65%
See 3 more Smart Citations
“…The explosive chromospheric evaporation model (Fisher et al 1985) explains the main observed characteristics of those events whose spatial scales are of the order of a few arcsec and last for a few minutes . The same scales are those obtained by the analysis of the background locations maintaining spatial resolution (Moretti et al 2001a). Recently, observations in Hα and NaI D lines have shown a simultaneous occurrence of the impulsive brightenings (Warmuth et al 2000;Moretti et al 2001b).…”
Section: The Observationssupporting
confidence: 65%
“…Left, from top to bottom a-d) a simulation at 1 minute cadence of the intensity and velocity impulses a), the power spectra of the signals b) and the intensity-velocity phase spectrum c) for a 9h zero-padded time-series. d) the observed phase spectra at l = 100 for the NaI D lines obtained with 256 min runs at Naples (crosses) and Kanzelhöhe (diamonds), Moretti et al (2001a). The main properties of the measured I − V phase spectrum is reproduced by the simulation based on the observed characteristics of the impulsive events detected with similar systems and at the same spatial resolution.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…5 and Fig. 1 in Moretti et al 2001). Results can depend on the techniques used by the different researches for the determination of the phase values, as described in Norton et al (2001).…”
Section: The Pixel-by-pixel Analysismentioning
confidence: 99%